2018
DOI: 10.3389/fbioe.2018.00072
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Likelihood of Gene Flow From Sugarcane (Saccharum Hybrids) to Wild Relatives in South Africa

Abstract: Pre-commercialization studies on environmental biosafety of genetically modified (GM) crops are necessary to evaluate the potential for sexual hybridization with related plant species that occur in the release area. The aim of the study was a preliminary assessment of factors that may contribute to gene flow from sugarcane (Saccharum hybrids) to indigenous relatives in the sugarcane production regions of Mpumalanga and KwaZulu-Natal provinces, South Africa. In the first instance, an assessment of Saccharum wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 83 publications
(115 reference statements)
2
13
0
Order By: Relevance
“…). Previous phylogenetic studies based on nuclear sequences (Hodkinson & al., ; Estep & al., ; Welker & al., ; Snyman & al., ) agree with our plastome results. The phylogenies of Hodkinson & al.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…). Previous phylogenetic studies based on nuclear sequences (Hodkinson & al., ; Estep & al., ; Welker & al., ; Snyman & al., ) agree with our plastome results. The phylogenies of Hodkinson & al.…”
Section: Discussionsupporting
confidence: 93%
“…() and Snyman & al. (), based on ITS sequence data, showed that a set of species of Tripidium (or Erianthus sect . Ripidium ) did not group closely with other members of Saccharum s.l.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, recent phylogenetic studies indicate that Tripidium is over 11 million years divergent, from Saccharum with Eriochrysis being even more divergent (Lloyd Evans et al, 2019)). Low copy number phylogenetics indicates that genus Sorghum is not monophyletic (Estep et al 2014, Lloyd Evans et al 2019 and ITS phylogenetics demonstrates that Microstegium is not monophyletic (Snyman et al 2018). Chloroplast-based phylogenetics diverges from low copy number phylogenetics and ITS-based phylogenetics (Lloyd Evans et al 2019, Snyman et al 2018 demonstrating that reticulate (network) evolution is commonplace in the Andropogoneae and the Saccharinae.…”
Section: Introductionmentioning
confidence: 99%